Challenges in Cataract Surgery Principles and Techniques for Successful Management - Kim, Wan Soo; Kim, Kyeong Hwan (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents the principles and pearls for successful surgical management of challenging situations encountered during cataract surgery. A wide range of settings are considered, including cataract surgery in patients with uveitis, traumatic cataract, dislocation of an intraocular lens, intumescent cataract, brunescent cataract, combined cataract and corneal disease, combined cataract and glaucoma, pediatric cataract, and refractive cataract surgery. In addition, preoperative factors conducive to a favorable surgical result are identified and appropriate management of postoperative complications, described. As longevity increases, cataract is becoming an even greater public health issue worldwide. The use of cataract surgery, already one of the most frequently performed surgeries, is consequently increasing still further - a trend reinforced by developments in instrumentation and technology and improvements in access to surgery. However, comorbidities and challenges during surgery are very common. Challenges in Cataract Surgery will be a valuable reference for all residents, fellows, and practicing ophthalmologists who wish to improve their surgical techniques and outcomes.